Cytotoxic activity of Goniothalamus umbrosus on oral squamous cell carcinoma - Che Aziz, Nuraini; Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon; Lestari, Widya (2023)
INTRODUCTION: The prevalence of oral cancer is increasing and has become a significant public health concern globally. This condition affects crucial functions such as eating, tasting, breathing, jaw movement, and speech, leading to serious health issues. In Malaysia, oral cancer is the nineteenth most frequently diagnosed cancer, with its occurrence varying depending on gender and ethnic group. G. umbrosus is consumed by Malaysian traditional folks for general well-being and to fight against tumour growth (Syahirah et al., 2016). To date, this plant has shown great anti-cancer potential against breast cancer cells, cervical cancer cells and leukemia cells (Toha et al., 2018; Sangrueng et al., 2015). RESEARCH GAP: However, to date, the cytotoxicity effect of this plant has never been tested on any oral squamous cell carcinoma cell lines. OBJECTIVE: This study aimed to evaluate the cytotoxic activity of G. umbrosus on oral squamous cell carcinoma cell line (SCC-15) and human gingival fibroblast cell line (HGF).